Legal challenges and political strategies in the post-truth era. Online hate speech trilogy (vol. 2) (2024)
This is the second book of the Online Hate Speech Trilogy. The work focuses on the legal challenges of combating toxic language and retaliating against those who spread hate on the Internet. Although the need for fighting violent narratives appears evident, given the role of hate in eroding trust and fragmenting the social fabric, there are many sensitive layers to the matter. The authors analyse the weaknesses of platform self-regulation, the European Union’s legal approach to combating online hate, the use of toxic language as a political weapon in Latin America, and the risks it poses to peace in Africa.